MOSS I: Double radio relics in the Saraswati supercluster. Issue 2 (23rd October 2021) - Parekh, V; Kincaid, R; Thorat, K; Hugo, B; Sankhyayan, S; Kale, R; Oozeer, N; Smirnov, O; Heywood, I; Makhathini, S; van der Heyden, K
ABSTRACT: Superclusters are the largest objects in the Universe, and they provide a unique opportunity to study how galaxy clusters are born at the junction of the cosmic web as well as the distribution of magnetic fields and relativistic particles beyond cluster volume. The field of radio astronomy is going through an exciting and important era of the Square Kilometer Array (SKA). We now have the most sensitive functional radio telescopes, such as the MeerKAT, which offers high angular resolution and sensitivity towards diffuse and faint radio sources. To study the radio environments around supercluster, we observed the (core part of) Saraswati supercluster with the MeerKAT. From our MeerKAT Observation of the Saraswati Supercluster (MOSS) project, the initial results of the pilot observations of two massive galaxy clusters, A2631 and ZwCl2341.1+0000, which are located around the dense central part of the Saraswati supercluster, were discussed. In this paper, we describe the observations and data analysis details, including direction-dependent calibration. In particular, we focus on the ZwCl2341.1+0000 galaxy cluster, which hosts double radio relics and puzzling diffuse radio source in the filamentary network. We have imaged these double radio relics in our high resolution and sensitive L -band MeerKAT observation and a puzzling radio source, located between relics, in the low-resolution image. We also derived the spectra of double radio relics using MeerKAT and archival GMRT observations. The following papers will focus on the formation of radio relics and halo, as well as radio galaxy properties in a supercluster core environment.